The effect of epicatechin on oxidative stress and mitochondrial damage induced by homocycteine using isolated rat hippocampus mitochondria - Fatemeh Shaki; Yaghoub Shayeste; Mohammad Karami; Esmaeil Akbari; Mahdi Rezaei; Ramin Ataee (Wolters Kluwer Medknow Publications, 2017)
Oxidative stress and mitochondrial dysfunction are the main suggested mechanisms for neurodegenerative diseases. In this study, we have evaluated the effects of epicatechin (EC) on mitochondrial damage induced by homocycteine (Hcy) using isolated rat hippocampus mitochondria in vivo. EC (50 mg/kg) was gavaged daily for a period of 10 days, starting 5 days prior to Hcy (0.5 μmol/μL) intra hippocampus injection in rats. Mitochondria were isolated from brain by different centrifuge techniques. Mitochondrial function was assayed by MTT test. Also, mitochondrial swelling and oxidative stress markers, such as reactive oxygen species (ROS), lipid peroxidation and glutathione (GSH), were assayed. Hcy induced mitochondrial dysfunction and swelling. Increase in ROS formation, lipid peroxidation, and decreased GSH were observed after Hcy treatment in isolated brain mitochondria. Furthermore, oral administration of EC significantly decreased the lipid peroxidation and ROS levels and also increased GSH levels. Also, EC treatment significantly improved mitochondrial function. As EC indicated protective effects against oxidative stress and mitochondrial damage induced by Hcy, it is suggested for further trials for prevention or treatments of neurodegenerative disorders such as Alzheimer disease.